Identification of Gastronomic Potential as a Tourist Attraction in the Tourism Village of Sukorejo, Sragen Regency, Central Java: Identifikasi Potensi Gastronomi sebagai Daya Tarik Wisata di Desa Wisata Sukorejo, Kabupaten Sragen, Jawa Tengah - Nurhayati, Hastuti; Hendrayana, Made; Rini, Faradila Anggun Surya (Politeknik Harapan Bangsa Surakarta, 2024)
This research aims to identify the potential of gastronomy as a tourist attraction in the Tourism Village of Sukorejo, Sragen Regency, Central Java. The research method used is qualitative, with data collection techniques including observation, in-depth interviews, and literature studies. The results of the research show that there are three types of local culinary offerings in Sukorejo Tourism Village, namely Tepo, Wedang Uwuh, and keripik Trewolo, which can become main attractions for tourists. These three culinary products each have unique characteristics in terms of flavor, presentation, and cultural or traditional significance. Another gastronomic aspect is the use of local raw materials in their processing, which supports the sustainability of the production process. These three types of local cuisine diversify tourism offerings by making keripik Trewolo preparation process a tourist attraction in itself. This research is essential for maximizing local potential and enhancing Sukorejo Village as a more attractive and sustainable tourist destination.